A rare cause of acute liver failure due to haemophagocytic lymphohistiocytosis secondary to diffuse large B-cell lymphoma - Coppola, Andrew (JRSM Open, 2021)
Acute liver failure is a life-threatening condition commonly caused by drug-induced hepatotoxicity or viral hepatitides. However, there are a number of rarer causes such as haemophagocytic lymphohistiocytosis. Haemophagocytic lymphohistiocytosis is a syndrome of uncontrolled immune cell activation, triggered by infection or malignancy, which carries a high mortality. Whilst mild to moderate liver injury is commonly seen with haemophagocytic lymphohistiocytosis, acute liver failure has rarely been reported in adults. We present a case of a 74-year-old man with acute liver failure secondary to haemophagocytic lymphohistiocytosis triggered by undiagnosed large B-cell lymphoma. Initially treated for biliary sepsis, there was a delay in the diagnosis of haemophagocytic lymphohistiocytosis and despite initiating chemotherapy, he died soon after. This case highlights the importance of considering haemophagocytic lymphohistiocytosis as a rare cause of acute liver failure, as given the life-threatening potential of haemophagocytic lymphohistiocytosis, a prompt diagnosis may allow early initiation of chemotherapy for any chance of survival.